The modification of split pontic as non-rigid connector in the management of pier abutment - Ivana; Syafrinani; Ricca Chairunnisa (Dentistry Faculty, 2020)
In long-span fixed partial denture restoration, especially when pier abutment is present, a non-rigid connector as a stress breaker is indicated. The Non-rigid connector is classified into a dovetail, loop connector, split pontic, cross-pin, and wing. Split pontic is an attachment placed entirely inside the pontic, particularly indicated in the tilted abutment case, to prevent the box preparation of distal pier abutment. This case report presents A pier abutment case treated with long span porcelain fused to the metal fixed movable bridge using dovetail shaped attachment, assembling the split pontic as a non-rigid connector. Split pontic acts as the stress breaker to prevent the pier abutment acts as a fulcrum. Split pontic also transfers the shear stress to the alveolar bone, minimalizes the mesiodistal torquing of the abutment teeth, and enables individual tooth movement. The advantages of this design are preparation with minimal reduction and better esthetic outcome as the porcelain build up can be done. Thus, there is no metal exposure of the restoration. Longevity and success of fixed partial denture restoration depend on the size, shape, type, and connector position. In pier abutment cases, a non-rigid connector must be considered one of the treatment choices to restore the missing teeth and preserve the abutments.KEYWORDS: pier abutment, split pontic, non-rigid connector